The Influence of Self-Efficacy and Organizational Citizenship Behavior (OCB) on Employee Performance Through Work Motivation as an Intervening Variable at the Banjarmasin City Education Office - Kamila Nurul Marhamah; Prima Jaya, Fanlia; Alfiannor, Alfiannor (Hut Publication Business and Management, 2025)
This study examines the effect of Self-Efficacy and Organizational Citizenship Behavior (OCB) on employee performance through work motivation as an intervening variable at the Department of Education in Banjarmasin City. The research uses a quantitative approach with survey methods. A total of 74 respondents, consisting of civil servants, were selected as samples using proportional sampling techniques. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results show that Self-Efficacy has a positive and significant effect on both work motivation and employee performance. OCB has a significant positive effect on work motivation but does not directly affect employee performance. Work motivation acts as an intervening variable linking Self-Efficacy and OCB with employee performance. The findings indicate the importance of strengthening employees’ self-belief and voluntary behavior through motivational improvement programs to enhance performance in public institutions.